English Catholicism Rethought? Rethinking Catholicism in Reformation England. By Lucy E. C. Wooding. (Oxford Historical Monographs.) Pp. x+305. Oxford: Clarendon Press, 2000. £40. 0 19 820865 0 - Armstrong, C. D. C. (The journal of ecclesiastical history, 2003)
The history of English Catholic theology between the break with Rome and the early years of the reign of Elizabeth I remains relatively little-known, despite (or perhaps because of) the publication of two recent American studies by P. S. O'Grady and E. A. Macek respectively: Henry VIII and the conforming Catholics, Collegeville, Minn. 1990, and The loyal opposition: Tudor traditionalist polemics, New York 1996. The appearance of a work which proposes to undertake a fresh survey of the whole period must therefore be welcomed.